Model Konseptual Pengaruh Influencer, Promosi, dan Persepsi Gaya pada Keputusan Pembelian Generasi Z - Haryanto Tanuwijaya; Vina Dwi Yanti (MDP Student Conference, 2026)
This This study aims to develop a conceptual model to explain the influence of influencers, digital promotion, and style perception on Generation Z’s purchase decisions in the fashion industry. The scope of the research focuses on purchasing behavior of sweetwear fashion products, which are trend-based and shaped by the digital ecosystem. This study employs a quantitative approach with an explanatory design through the development of a conceptual model based on a synthesis of recent literature. The model integrates external factors, namely influencers and digital promotion, with an internal factor, namely style perception. The findings indicate that influencers act as social reference sources that build trust, digital promotion increases exposure and perceived value, while style perception strengthens the alignment between products and Generation Z’s self-identity. The study concludes that Generation Z’s purchase decisions are multidimensional and influenced by the interaction of social, digital, and symbolic factors, making this conceptual model relevant as a foundation for future empirical research.